Transnational Understanding and Its Impact on Diversity in Indonesia - Hadiyanto, Andy; Anggraeni, Dewi; Rusyd, Ibnu (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
In this paper, we will examine the philosophical and psychological reasons regarding the thoughts and activities of transnational movements as to what makes these transnational Islamic movements so easy to captivate the hearts of Muslims in Indonesia. The method used in this research is descriptive qualitative with a literature study approach by referring to primary sources of books related to transnational Islam. This study indicates that transnational Islam is the embodiment of revivalism which beliefs in the overall teachings of Islam. Transnational Islam, in turn, can transform into Islamism, an Islamic political movement, or remain committed to its da’wah and social movements. The first is a movement that seeks to achieve power legally and constitutionally in a secular state system. The second is a movement that refuses to recognize the secular system and seeks to peacefully gain power from outside the system. The third is a movement that seeks to gain power by force, both at the level of discourse and action.